ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT WAJIB PAJAK UNTUK BERPERILAKU PATUH (Stdudi Empiris Tax Payer Wajib Pajak Badan di KPP Pratama Batang) - Iswari Rizqi Respati, 10.05.52.0128; Meita, Rachmawati (Students Journal of Accounting and Banking, 2014)
This study aims to examine and analyze of factors that affect tax payer intention to behave obediently. Population in this study is tax payer in KPP Pratama Batang. The selection for sampling method is convenience sampling or sampling which selection by easyer. The samples echievement is 86 respondents. Technique analyze for data is multiple linear regression. Finding ofÂ this research indicated the effect of attitude and perceived behavioral control influential toward tax payer intention to behave obdiently, subjective norm not influential toward tax payer intention to behave obdiently.Keywords: Attitude, Subjective Norm, Perceived Behavioral Control, Intention, Tax Compliance